1985
DOI: 10.1021/bi00343a009
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of protein synthesis initiation factor eIF-4E from the yeast Saccharomyces cerevisiae

Abstract: A 24 000-dalton protein [yeast eukaryotic initiation factor 4E (eIF-4E)] was purified from yeast Saccharomyces cerevisiae postribosomal supernatant by m7GDP-agarose affinity chromatography. The protein behaves very similarly to mammalian protein synthesis initiation factor eIF-4E with respect to binding to and elution from m7GDP-agarose columns and cross-linking to oxidized reovirus mRNA cap structures. Yeast eIF-4E is required for translation as shown by the strong and specific inhibition of cell-free transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 27 publications
1
63
0
Order By: Relevance
“…2). We individually replaced the tryptophans in 4EHP that are conserved between 4EHP and eIF4E (Trp 63 A similar effect was observed when the corresponding amino acids were substituted in yeast eIF4E (51). This suggests that the nature of the aromatic ring of the carboxyl-distal aromatic amino acid is more important than the amino-proximal amino acid.…”
Section: Amino Acid Residues Required For Cap Bindingmentioning
confidence: 77%
“…2). We individually replaced the tryptophans in 4EHP that are conserved between 4EHP and eIF4E (Trp 63 A similar effect was observed when the corresponding amino acids were substituted in yeast eIF4E (51). This suggests that the nature of the aromatic ring of the carboxyl-distal aromatic amino acid is more important than the amino-proximal amino acid.…”
Section: Amino Acid Residues Required For Cap Bindingmentioning
confidence: 77%
“…1A) were recently shown to be involved in the binding of m 7 GDP by solving the structures of mouse eIF4E and yeast eIF4E with bound m 7 GDP (4, 5). Mutagenesis studies with yeast (28) and human (29) eIF4E indicated that mutation of the conserved Trp residues (with the exception of Trp 4 in yeast) either eliminated or reduced the ability of eIF4E to bind m 7 G affinity columns. It was, therefore, of great interest to determine if the nCBP, which is lacking Trp-1 and -3, is able to bind m 7 G functional groups.…”
Section: Resultsmentioning
confidence: 99%
“…Extracts of E. coli Y1090 cells infected with Xgtll or Xgtll recombinant bacteriophage B17 and B46 were prepared as described above and chromatographed on 1-ml m7GDP-agarose columns as described before (1,6 (10). Total DNA was cut with the restriction enzyme EcoRI and cDNA inserts were ligated into M13mpl8 (19).…”
Section: Methodsmentioning
confidence: 99%
“…The factor resembles its mammalian homolog in terms of molecular weight, binding to m7GDP-agarose affinity columns, and cross-linking to oxidized reovirus mRNA (1). The mammalian and yeast proteins are, however, immunologically distinct (1).…”
mentioning
confidence: 96%
See 1 more Smart Citation